2018
DOI: 10.1007/s12186-018-9203-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Students’ Transitions to Successive VET Levels through Continuing Learning Pathways

Abstract: Continuing learning pathways have been proposed as curriculum design solutions to reduce student drop-out rates and to promote their transitions to successive levels of the educational system. The present study aimed to compare the effects of a specific continuing learning pathway in Dutch VET (the Green Lyceum or GL, which combines a lower secondary pre-vocational school-based (VMBO) programme and a middle-management VET (MBO) programme in an integrated learning trajectory offered by agricultural (or 'green')… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Several researchers have suggested (e.g., Cardinal, 2010;Cents-Boonstra et al, 2018;Dubeau et al, 2017;Biemans et al, 2019) that VET programs attract less motivated students, and studies on VET motivational and SRL strategies are therefore not priority areas for exploration. To us, this opens a door to new research, which might focus on the Catalan context using the preliminary validated scales to compare motivation levels and SRL strategies between VET and high-school or university students-these being similar in age but differing in levels of motivation (Martin, 2008).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Several researchers have suggested (e.g., Cardinal, 2010;Cents-Boonstra et al, 2018;Dubeau et al, 2017;Biemans et al, 2019) that VET programs attract less motivated students, and studies on VET motivational and SRL strategies are therefore not priority areas for exploration. To us, this opens a door to new research, which might focus on the Catalan context using the preliminary validated scales to compare motivation levels and SRL strategies between VET and high-school or university students-these being similar in age but differing in levels of motivation (Martin, 2008).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The present study will focus on the GL as a possible alternative pathway to HBO. Previous research (Biemans et al, 2019) already demonstrated that former GL students more often proceeded with an HBO programme than comparable students coming from regular MBO. The central aim of the present study was to examine former GL students' experiences in HBO and to compare those with the experiences of students coming from the two traditional routes to HBO mentioned above.…”
Section: Introductionmentioning
confidence: 95%
“…Transitions between successive educational levels of the VET system (but also in other segments of the educational system) appear to be problematic for many students. As described by Biemans et al (2019), this phenomenon has been analysed in the international literature on the permeability of educational systems (e.g., Bathmaker & Thomas, 2009;Bradley, 2008;Gorard et al, 2006;Watson, 2006). One of the key aspects of permeability of educational systems is the 'capacity of education and training systems to enable learners to access and move among different pathways (programmes, levels) and systems' (Cedefop, 2014, p. 193).…”
Section: Transition To and Drop-out From Higher Professional Bachelormentioning
confidence: 99%
See 2 more Smart Citations